INOVASI PADA PELAYANAN PUBLIK: MENUJU PEMERINTAHAN YANG MELEK DIGITAL - Rafli Mahrum; Bagus Rangga Prayoga; Hayat, Hayat (Triwikrama: Jurnal Ilmu Sosial, 2025)
Public service innovation is important in the implementation of public services. In the current digital era, it is necessary to innovate digitally based public services because this is in line with demands for bureaucratic reform to create a clean, transparent and accountable government. Through digitalization of public services, it also makes it easier for the government to achieve effectiveness and efficiency and can lead to becoming a digital-based government. The involvement of State Civil Apparatus (ASN) is very important in developing innovation. This is in line with ASN's core value, namely having morals, where there is a demand for ASN to have competence in operating technology, information and communication (ICT). Digital literacy skills also support digitalization in government. This research aims to analyze forms of innovation in public services and the efforts made to move towards a digitally literate government. The research results show that regions in Indonesia have begun to implement digital-based public service innovations in the form of applications and websites. The government has also formed a strategy to build digital culture within the government through various training provided to ASN, one of which is through increasing digital literacy. The government is also collaborating with various parties to support the successful implementation of government digitalization, both with internal and external parties.